Estrategias de acompañamiento desde las habilidades blandas a padres de familia de los niños de inclusión de grado primero del Colegio Distrital Carlos Pizarro Leongómez, localidad séptima de Bogotá, D.C. - Pineda Forero, Ana; Valero Suárez, Sandra Hasbleydi (Universidad Antonio Nariño, 2023)
In Colombia, the responsibility for the educational process falls on the State, society and the family. Hence the concept of co-responsibility that is exposed from the jurisprudence. For this reason, in the most recent decade efforts have been joined so that, without any kind of distinction, all Colombians have access and permanence in the educational system. This is how the educational inclusion process is changing the ways of seeing and living the school: it has given way to the elimination of barriers in the teaching-learning process and a new way of living has been proposed. In practice, it has been shown that family accompaniment in the academic process is of vital importance, even more so, when the student has a disability.